OPTIMALISASI PEMBELAJARAN MATEMATIKA SECARA DIGITAL MELALUI WEBSITE MATHEXIA.ORG: OPTIMIZING DIGITAL MATHEMATICS LEARNING THROUGH THE MATHEXIA.ORG WEBSITE - Rike Marjulisa; Ayunda Putri; Yusa Putra; Nanditya Syahmi Khan; Devan Aptinsyah (LPPM Universitas Abdurrab, 2025)
The utilization of digital technology in mathematics learning is very important to improve the quality of the learning process. This service activity aims to introduce and implement Mathexia.org, a digital question bank website, for he Senior High School Mathematics Teacher Forum (MGMP) of Pelalawan Regency. This platform allows teachers to input questions and materials, access question banks between schools, and organize token and time-based exams. Students can access materials, take exams, view results, and review questions for further study. Implementation methods included teacher training and the use of a student questionnaire with a four-point Likert scale, which was analyzed descriptively quantitatively. Results from 140 students showed positive improvements in learning motivation, digital literacy, and effectiveness of material comprehension after using Mathexia.org. This activity proves that this website can be an innovative solution in supporting more modern math learning in Kabupaten Pelalawan.